2021
DOI: 10.1001/jama.2021.4152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermediate-Dose vs Standard-Dose Prophylactic Anticoagulation on Thrombotic Events, Extracorporeal Membrane Oxygenation Treatment, or Mortality Among Patients With COVID-19 Admitted to the Intensive Care Unit

Abstract: IMPORTANCE Thrombotic events are commonly reported in critically ill patients with COVID-19. Limited data exist to guide the intensity of antithrombotic prophylaxis.OBJECTIVE To evaluate the effects of intermediate-dose vs standard-dose prophylactic anticoagulation among patients with COVID-19 admitted to the intensive care unit (ICU). DESIGN, SETTING, AND PARTICIPANTSMulticenter randomized trial with a 2 × 2 factorial design performed in 10 academic centers in Iran comparing intermediate-dose vs standard-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
444
2
25

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(490 citation statements)
references
References 42 publications
19
444
2
25
Order By: Relevance
“…Research on therapeutic anticoagulation in critically ill patients with COVID-19 is still ongoing (appendix p 1; preprint). 42 Data from the INSPIRATION trial, 47 Hence, based on results from the INSPIRATION trial, there is no rationale for the current widely used intermediate dose of low-molecular-weight heparin as thrombosis prophylaxis in critically ill patients with COVID-19. Notably, this study was designed by an international committee and was done in ten centres in Iran, which might affect the generalisability to other countries and health-care systems.…”
Section: Icu Patients (Stage 3)mentioning
confidence: 99%
“…Research on therapeutic anticoagulation in critically ill patients with COVID-19 is still ongoing (appendix p 1; preprint). 42 Data from the INSPIRATION trial, 47 Hence, based on results from the INSPIRATION trial, there is no rationale for the current widely used intermediate dose of low-molecular-weight heparin as thrombosis prophylaxis in critically ill patients with COVID-19. Notably, this study was designed by an international committee and was done in ten centres in Iran, which might affect the generalisability to other countries and health-care systems.…”
Section: Icu Patients (Stage 3)mentioning
confidence: 99%
“…Previous research suggested that the incidence of thrombotic complications in ICU patients with COVID-19 infections is remarkably high despite anticoagulant therapy at standard prophylactic dose [49] . Notwithstanding this, recent evidence on patients admitted to the ICU with COVID-19 showed that intermediate-dose prophylactic anticoagulation did not result in a significant difference in the primary outcome of a composite of adjudicated venous or arterial thrombosis, treatment with extracorporeal membrane oxygenation, or mortality within 30 days [50] . This might also hold true as for SVT.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) was frequently observed in acutely ill patients with COVID-19 during the early stages of the pandemic, approaching a proportion of one-third of patients in the ICU, even when prophylactic anticoagulation was used [ 8 ]. In a recent study published in JAMA, Sadeghipour et al have reported the results of a multicenter RCT of intermediate-dose versus standard-dose heparin-based thromboprophylaxis in critically ill patients with COVID-19 [ 20 ]. Among 562 inpatients enrolled, no significant difference in the primary efficacy outcome was ascertained [a composite of venous or arterial thrombosis, treatment with extracorporeal membrane oxygenation (ECMO)], or mortality within 30 days of enrollment) or in the main safety outcomes, such as major bleeding and severe thrombocytopenia between the two groups.…”
Section: What Do We Have So Far In Our Armamentarium?mentioning
confidence: 99%
“…However, there are several issues worth mentioning mainly regarding the low thrombotic event rate reported in both study groups, raising the possibility of a considerable number of potentially “missed” cases. VTE rates reported in clinical studies regarding COVID-19 have substantially varied, with higher rates noted in early investigations and in studies that used VTE screening and lower rates reported in more recent investigations and in studies that did not screen for VTE [ 20 ]. Sadeghipour et al did not use universal screening for VTE.…”
Section: What Do We Have So Far In Our Armamentarium?mentioning
confidence: 99%